Nickel‐Catalyzed Enantioselective Reductive Amination of Ketones with Both Arylamines and Benzhydrazide. Issue 39 (30th August 2016) - Yang, Peng; Lim, Li Hui; Chuanprasit, Pratanphorn; Hirao, Hajime; Zhou, Jianrong (Steve)
Abstract: An asymmetric reductive amination of ketones using both arylamines and benzhydrazide in the presence of nickel catalysts was developed. A one‐pot synthesis of tetrahydroquinoxalines was also developed starting directly from α‐ketoaldehydes and 1, 2‐diaminobenzene. Formic acid was used as a safe and economic surrogate for high‐pressure hydrogen gas. Strongly σ‐donating bis(alkylphosphine)s are crucial ancillary ligands for both stereoselective hydride insertion and decarboxylation of the formate. Abstract : Reducing costs : Reductive amination of ketones with both arylamines and benzhydrazide was realized in the presence of catalysts based on nickel rather than expensive noble metals. Formic acid was used as a safe and cheap surrogate for high‐pressure hydrogen gas.